Scientific communication in 2011 - Aleixandre-Benavent, Rafael (Anuario ThinkEPI, 2012)
An analysis of the situation of scientific communication in 2011 highlights some of the more relevant events, news and issues. Topics discussed include: the open access initiative and institutional repositories, semantic interoperability and linked data, use of the internet, right to information, rise of professional and academic profiles on the Web, trends in bibliometric indicators, consolidation of national scientific evaluation tools, trends observed in conferences and congresses, and the race for rankings in scientific publication between the United States, China and Europe.
Keywords: Scientific communication; Open access; OA; Repositories; Linked data; Internet use; Bibliometrics; Professional and research profiles.